A Case of Systemic Lupus Erythematosus/Antineutrophil Cytoplasmic Antibody-Associated Vasculitis Overlap Syndrome with Dissociated Pathological and Immunological Findings - Kazuhiko Kato; Tetsuya Kawamura; Risa Terashima; Yukiko Tsuchiya; Yasuhito Takahashi; Kenji Kasai; Takashi Yokoo (Case Reports in Nephrology)
Systemic lupus erythematosus/antineutrophil cytoplasmic antibody-associated vasculitis overlap syndrome (SLE/AAV OS) describes a pathological condition that presents with overlapping features of two diseases. There have been few reports of SLE/AAV OS and none from Japan. We present the case of a 59-year-old woman admitted with chief complaints of fever and decreased renal function. SLE was suspected due to the identification of four items from the diagnostic criteria of the American College of Rheumatology, including positivity for anti-ds-DNA and antinuclear antibodies. However, pathological findings from the kidney biopsy suggested pauci-immune crescentic glomerulonephritis. She was also diagnosed with AAV according to the Chapel Hill Consensus Conference (CHCC) 2012 definitions and the classification algorithm of AAV. SLE/AAV OS was suspected, we started immunosuppressant therapy, and subsequently her renal function improved. In previous reports, initial immunological and pathological findings generally concur. In cases where clinical and pathological features appear to conflict, as in the present case, a treatment strategy decision should be based on pathological and immunological findings to improve the prognosis of OS.